Evaluación final de Informática Médica para la formación de habilidades investigativas en estudiantes de medicina. - Ortiz Romero, Gemma Margarita; Soto Santiesteban, Vivian; Felicó Herrera, Gilberto; Rodríguez Neyra, María Emilia; Soto Santiesteban, Beatriz (MEDISAN, 2019)
A descriptive study was carried out in Holguín Medical Sciences Faculty, from January, 2017 to the same period in 2018, with the aim of characterizing the process of final evaluation of the Medical Computer discipline corresponding to the study plan D for the development of investigative skills in the medicine students. The universe was constituted by the results of the final work of the subjects Computer science, Biostatistics and Methodology; the sample was constituted by the 40 final works of Methodology of Investigation which had the greatest difficulties in the written report and by 16 professors of Medical Computer science. The documental review, observation and interview were used. Absolute values and percentages were calculated. The results of the final work showed excellent promotion. The indicator defense was that of greatest difficulty with 60.0% of the evaluated works as average and poor. The final evaluation contributed to the development of the investigative skill.